Gremlin 2 Promotes Differentiation of Embryonic Stem Cells to Atrial Fate by Activation of the JNK Signaling Pathway. (17th June 2014) - Tanwar, Vineeta; Bylund, Jeffery B.; Hu, Jianyong; Yan, Jingbo; Walthall, Joel M.; Mukherjee, Amrita; Heaton, William H.; Wang, Wen-Der; Potet, Franck; Rai, Meena; Kupershmidt, Sabina; Knapik, Ela W.; et al.
Abstract : The bone morphogenetic protein antagonist Gremlin 2 (Grem2) is required for atrial differentiation and establishment of cardiac rhythm during embryonic development. A human Grem2 variant has been associated with familial atrial fibrillation, suggesting that abnormal Grem2 activity causes arrhythmias. However, it is not known how Grem2 integrates into signaling pathways to direct atrial cardiomyocyte differentiation. Here, we demonstrate that Grem2 expression is induced concurrently with the emergence of cardiovascular progenitor cells during differentiation of mouse embryonic stem cells (ESCs). Grem2 exposure enhances the cardiogenic potential of ESCs by 20–120-fold, preferentially inducing genes expressed in atrial myocytes such as Myl7, Nppa, and Sarcolipin . We show that Grem2 acts upstream to upregulate proatrial transcription factors CoupTFII and Hey1 and downregulate atrial fate repressors Irx4 and Hey2. The molecular phenotype of Grem2-induced atrial cardiomyocytes was further supported by induction of ion channels encoded by Kcnj3, Kcnj5, and Cacna1d genes and establishment of atrial-like action potentials shown by electrophysiological recordings. We show that promotion of atrial-like cardiomyocytes is specific to the Gremlin subfamily of BMP antagonists. Grem2 proatrial differentiation activity is conveyed by noncanonical BMP signaling through phosphorylation of JNK and can be reversed by specific JNK inhibitors, but not by dorsomorphin, an inhibitor of canonical BMP signaling. Taken together, our data provide novel mechanistic insights into atrial cardiomyocyte differentiation from pluripotent stem cells and will assist the development of future approaches to study and treat arrhythmias. Stem Cells 2014;32:1774–1788